Оцінка впливу природно-антропогенних змін потоків CO2 у системі рослинність — атмосфера на формування парникового ефекту Землі - Лялько, В.І. (Видавничий дім "Академперіодика" НАН України, 2007)
The analysis of the current approaches to the ''Earth's greenhouse effect'' prediction is performed. A new methodology has been proposed to estimate the ''greenhouse effect'' and its change on the basis of the ground experimental CO2 flow measurements and the satellite data analysis. The many-year variations of the areas occupied by different vegetation species with different photosynthetic activity features are considered. The CO2 flow values are determined and are converted into the ''greenhouse'' temperature analogs which can be used in the models of energy-mass exchange in the geospheres of the Earth for the computer forecasting of global and regional changes of the climate.